Effect of drying methods on free and bound phenolic compounds, antioxidant capacities, and bioaccessibility of Cornelian cherry - Bayram, Hatice Merve; Ozkan, Kubra; Ozturkcan, Arda; Sagdic, Osman; Gunes, Esra; Karadag, Ayse (SPRINGER, 2024)
Cornus mas L. (Cornelian cherry, CM) fruits were dehydrated by solar-drying (SD) and freeze-drying (FD), and in addition to sugar and mineral contents, the free and insoluble-bound phenolics were determined in fresh and dried fruits. After subjecting the sample to simulated in vitro digestion, the change of free and bound phenolics at gastric and intestinal digestion steps was evaluated in fresh and dried CM fruits. In fresh CM fruits, the total phenolic content (TPC) was dominated by the bound fraction, whereas the contribution of free phenolics to the total content (free + bound) became more dominant (731-1439 mg GAE/100 g dw) in the dried fruits. The bioaccessibility (BI%) of TPC from fresh CM after digestion was 193%, whereas it was 18.60 and 48.02% for SD and FD fruits, respectively. The contribution free fraction to the total TPC value was around 28% in nondigested fresh samples and increased to 94% in digested samples; however, in dried samples, it was 64% prior to digestion and only increased to 70% in digested samples. A total of 17 phenolic compounds were identified in CM fruits: chlorogenic acid, caffeic acid, epicatechin, quercetin, cyanidin-3-O-glucoside, and pelargonidin 3-O-glucoside were only detected in the free fraction; gallic acid, vanillic acid, ferulic acid, and kaempferol were detected in higher amounts in the bound fraction. The quantity of detected phenolics in the nondigested sample generally decreased from the gastric to the intestinal stage of digestion. The release of phenolics from the fruit matrix and their degradation occurred simultaneously during digestion, and this could be affected by the state of the fruit, e.g., fresh or dried.
Keywords: Cornus mas L.; Free phenolics; Insoluble-bound phenolics; Antioxidant capacity; Simulated digestion; CORNUS-MAS L.; IN-VITRO; POLYPHENOLS; IMPACT; FRUITS; GREEN; Food Science & Technology